2013
DOI: 10.2139/ssrn.2340509
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Energy Mix in Power Generation and the Contribution from Natural Gas in Reducing Carbon Emissions to 2030 and Beyond

Abstract: This paper analyses a set of new scenarios for energy markets in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…He concluded that the economic potential of all RES cannot be used at the same time, because the full use of the economic potential of one RES reduces the economic potential of others, and the EXPANSE tool is used to analyze these interrelations. In the paper (Carraro et al, 2013), a set of scenarios for European energy markets is analyzed so as to assess economic incentives and climate goals. The scenarios' analysis was performed using the World Induced Technical Change Hybrid Model (WITCH), which is used in the global assessment of climate and energy policies.…”
Section: Economic Optimized Energy MIXmentioning
confidence: 99%
See 1 more Smart Citation
“…He concluded that the economic potential of all RES cannot be used at the same time, because the full use of the economic potential of one RES reduces the economic potential of others, and the EXPANSE tool is used to analyze these interrelations. In the paper (Carraro et al, 2013), a set of scenarios for European energy markets is analyzed so as to assess economic incentives and climate goals. The scenarios' analysis was performed using the World Induced Technical Change Hybrid Model (WITCH), which is used in the global assessment of climate and energy policies.…”
Section: Economic Optimized Energy MIXmentioning
confidence: 99%
“…Previous research has been mainly based on the analysis of RES integration into the power system of countries, regions, with one of the following target functions: minimizing the generation of surplus electricity, minimizing installed capacity, while minimizing total costs. The economic criteria used in the research Carraro et al (2013), Lund (2014) and Haller et al (2012) relate to the reduction of costs of: investment, operation and maintenance, fuel, electricity, net present value, repayment period, lifetime, equivalent annual cost, etc.…”
Section: Economic Optimized Energy MIXmentioning
confidence: 99%